SIMILARITAS FORMALISME DENGAN POLA VISUAL ALAMI PADA ANYAMAN BAMBU PRODUK BAITUL QURRO, DESA GINTUNG CILEJET, BOGOR: SIMILARITY OF FORMALISM WITH NATURAL VISUAL PATTERNS IN BAMBOO WEAVING PRODUCTS FROM BAITUL QURRO, GINTUNG CILEJET VILLAGE, BOGOR - Dikdik Adikara Rachman (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
Traditional woven bamboo products contain formal values ​​of design principles that have similarities with natural visual patterns. Through these similarities, it is clear that traditional bamboo woven products are a process of internalizing various natural visual patterns to become aesthetic manifestation and functional. The aesthetic manifestation is explained in the stages of the internal process of culture in the context of Sundanese tradition. The topic is viewed from the perspective of fine art and design taken from the Rural Community Empowerment Program in Baitul Qurro, Gintung Cilejet Village, Bogor Regency, which runs from June to November 2023. The program is implemented by the Center for Visual and Environmental Design Studies, FSRD Usakti.